2020
DOI: 10.1002/mp.14229
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an organic semiconductor diode for dosimetry in radiotherapy

Abstract: The development of novel detectors for dosimetry in advanced radiotherapy modalities requires materials that have a water-equivalent response to ionizing radiation such that characterization of radiation beams can be performed without the need for complex calibration procedures and correction factors. Organic semiconductors are potentially an ideal technology in fabricating devices for dosimetry due to tissue-equivalence, mechanical flexibility and relatively cheap manufacturing cost. The response of a commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…suggested to be the reason for such divergence from the expected results (Posar et al, 2020b). The maximum photocurrent from the OPD for the Al-Al filter was 100Â larger than that of the Cu-Al and Cu-Cu filters.…”
Section: Figurementioning
confidence: 84%
See 1 more Smart Citation
“…suggested to be the reason for such divergence from the expected results (Posar et al, 2020b). The maximum photocurrent from the OPD for the Al-Al filter was 100Â larger than that of the Cu-Al and Cu-Cu filters.…”
Section: Figurementioning
confidence: 84%
“…At doses of 35 kGy or higher, the variation of any subsequent changes in charge output was observed to be <0.5%, suggesting that the radiation effects stabilize past this point and the detector can be used in such high-dose-rate radiation fields for MRT applications. Our previous work has shown that such exposure to X-rays in the energy range of interest for MRT degrades the absorption spectrum of the acceptor and donor materials of the sensitive volume above wavelengths of 450 nm (Posar et al, 2020b).…”
Section: Radiation Damagementioning
confidence: 99%
“…The flexibility makes organic film based electronic devices superior over its inorganic counter parts. For flexible device applications such as power sources [74,75], displays [76], electronics [77], super capacitors [78], gas sensors [79][80][81], thermoelectric power generators [82,83], organic light emitting diodes [84,85], radiation dosimeters [86][87][88] etc., organic semiconductors are promptly used. The nature of interaction between high energy EB and organic materials depends on the energy as well as dose of the incident EB [7].…”
Section: Organic Semiconductors and Its Interaction With Electron Beammentioning
confidence: 99%
“…Consequently, their use for medically relevant dosimetry or personal health monitoring requires complex, often unreliable calibrations limiting their applications in radiotherapy or food sterilization. [ 8 ] A new generation of materials for X‐ray sensing must therefore be envisaged, combining a tissue equivalent response with other ideal properties such as mechanical flexibility, low operating power requirements, and real‐time response rates.…”
Section: Introductionmentioning
confidence: 99%